A different approach to PCOS: evaluation of spermiogram results in male patients with a family history of PCOS - Mujde Can Ibanoglu; Ayse Gizem Yildiz; Ozde Beren Tatar; Berna Seckin; Tufan Cicek; Yaprak Engin-Ustun (Gynecological Endocrinology)
Objective The aim of this study was to investigate the possible influence of a family history of PCOS on male reproductive health by comparing the spermiogram parameters of patients diagnosed with a first-degree relative with PCOS with those of a control group without such a family history.Methods This prospective study included 51 male participants aged 19–39 years, 25 of whom had a first-degree relative diagnosed with PCOS, while 26 formed the control group. Semen samples were collected and analyzed according to the World Health Organization (WHO) 2021 guidelines.Results In this study, the spermiogram results of 51 patients aged between 19 and 39 years with a mean age of 31.50 ± 4.80 years were analyzed. The median sperm concentration (0.6 vs. 11.1 million/ml; p = 0.024) was significantly lower in the study group and the median total progressive motile sperm concentration (3.7 vs. 3.0 million/ml; p = 0.010) was significantly lower in the control group. Comorbidities were more common in the study group, including hair loss (64%; p < 0.001) and gynecomastia (25%; p = 0.008). Robust regression analysis revealed that semen concentration was significantly higher in subjects with dyslipidemia (+95.973 million/ml; p < 0.001), as was sperm motility (+49.081 units; p < 0.001) and TPMSC (+74.028 million/ml; p < 0.001).Conclusion Men with family history of PCOS have distinct reproductive and metabolic features, including lower median sperm concentration and higher incidence of alopecia and gynecomastia. Dyslipidemia significantly predicted improved sperm concentration and motility.